2018
DOI: 10.1098/rspb.2018.0318
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of biannual moulting strategies across birds and mammals

Abstract: Birds and mammals have developed numerous strategies for replacing worn feathers and hair. Moulting usually occurs on an annual basis; however, moults that take place twice per year (biannual moults) also occur. Here, we review the forces driving the evolution of various moult strategies, focusing on the special case of the complete biannual moult as a convergence of selection pressures across birds and mammals. Current evidence suggests that harsh environmental conditions or seasonality (e.g. larger variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 118 publications
(182 reference statements)
4
60
0
Order By: Relevance
“…All adult birds with new tertials had been collected in just four months: August to November. The latter is typical of seasonally homogeneous areas, whereas a biannual molt is typical of temperate latitudes with cold winters and hot summers: precisely the environmental conditions experienced by a majority of Palearctic larks (Beltran et al 2018). In fact, this wearing pattern was previously suggested in Cramp (1988), who described consistent differences in the freshly molted autumn feathers of all 21 lark species in the Western Palearctic compared to their worn spring plumage.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…All adult birds with new tertials had been collected in just four months: August to November. The latter is typical of seasonally homogeneous areas, whereas a biannual molt is typical of temperate latitudes with cold winters and hot summers: precisely the environmental conditions experienced by a majority of Palearctic larks (Beltran et al 2018). In fact, this wearing pattern was previously suggested in Cramp (1988), who described consistent differences in the freshly molted autumn feathers of all 21 lark species in the Western Palearctic compared to their worn spring plumage.…”
supporting
confidence: 60%
“…In fact, this wearing pattern was previously suggested in Cramp (1988), who described consistent differences in the freshly molted autumn feathers of all 21 lark species in the Western Palearctic compared to their worn spring plumage. Outside the Sylvioidea, the species known to have a single annual molt in the Palearctic are all the Sturnidae, the Passeridae, Miliaria calandra in Emberizidae (Svensson 1992), and Pyrrhula pyrrhula and Carduelis flammea cabaret in Fringillidae (Beltran et al 2018). By contrast, the non-lark passerines in our sample, including the closely related Bearded Reedlings, presented fresh and unworn tertial feathers across the year.…”
mentioning
confidence: 70%
“…The review by Ling () also reported that malnutrition delayed molt in various wild mammals (e.g., black‐tailed deer, caribou ( Rangifer tarandus groenlandicus ), and elephant seal ( Mirounga leonida )). Moreover, temperature is another external cue that can interact with photoperiod to modulate the timing of molt (Beltran et al, ; Zimova et al, ). Colder temperatures can delay molt completion, a tendency we observed for mountain goats.…”
Section: Discussionmentioning
confidence: 99%
“…Pelage provides concealment, thermoregulation, and protection, and is therefore a key component for mammals facing harsh climatic conditions in northern environments (Caro, ; Cowan & Raddi, ; Zimova, Mills, Lukacs, & Mitchell, ; Zimova, Mills, & Nowak, ). Several species exposed to large temperature variations in their environment grow and molt one or two annual coats (one for summer and one for winter; Maurel, Coutant, Boissin‐Agasse, & Boissin, ; Beltran, Burns, & Breed, ). Growing and molting new hairs involve energetic costs (Boyd, Arnbom, & Fedak, ; Neuhaus, ), particularly after winter, a period associated with high energetic expenses and limited resources for herbivores (Stewart, Bowyer, Dick, Johnson, & Kie, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation